Studi Diagnostik Menggunakan PCR untuk Mendeteksi Virus Hepatitis C Dalam Cairan Air Mata Pasien Hemodialisis - Purwanita, Petty; Natsir, Novia (Sriwijaya Journal of Medicine, 2021)
Patients Hepatitis C virus (HCV) is a hepatotropic and lymphotropic virus. Patients infected with HCV might develop at least one extrahepatic manifestation ocular and in the lacrimal sac during the course of their disease. HCV transmission occurs through exposure to blood contaminated with high risk factor in hemodialysis patients about 70%. Detection RNA HCV more sensitive and specific by PCR (Polymerase Chain Reaction). This study evaluated the sensitivity and specificity of PCR hepatitis c virus in tears hemodialysis patients at Mohammad Hoesin Palembang. This is an observational diagnostic study of 25 samples from tears and blood in hemodialysis patients. PCR examined by RT-PCR. The data obtained were analyzed by a diagnostic test. Of 25 samples HCV-RNA was detected by PCR in the tears 11 cases were positive (44%) and 20 cases were found positive (80%) in plasma. The value of the sensitivity of the tears is 72.73% and the specificity was 13.33%. Tears fluid specimen quite sensitive but not specific, therefore PCR examination can be used for screening for hepatitis C virus in hemodialysis patients.